Religion, technology and cooperative rationality: a philosophical approach - Silalahi, Ubat Pahala Charles (Journal for the study of religions and ideologies, 2024)
The conflict between religion and science reached its peak after the Enlightenment. People today exhibit a greater inclination towards science as compared to religion. Religion's influence in shaping human progress diminished as science gained favor. Following over a half-century of strained ties, a movement arose that opposed the growing hostility between religion and science. Today, the era of digital disruption has become part of human civilization. As a result of scientific progress, information technology requires reconciliation with faith. After all, religion needs secular methods and ideas for its advancement. So, this paper offers a new type of entanglement between religion and technology based on cooperative rationality. Cooperative rationality considers reason as the foundation, then cooperation as the next step. Because religion and technology both rely on human reason, with cooperative rationality, religion and technology can find complex, coordinated actions that allow both to benefit. So, organized scientific inquiry is not merely for taking on intellectual tasks but also for humanity. Cooperative rationality relies on fundamental intellectual concerns to pay more attention to technological goals, considering scientific and human values.